(untitled) (Al-Aasar, 2025)
The tradition of addressing contemporary issues in Urdu literature has deep roots in the socio-political transformations of the subcontinent. Urdu fiction, particularly novels and short stories, has consistently mirrored the evolving dynamics of society, including themes such as poverty, gender discrimination, class conflict, feudal oppression, migration, and identity crises. Early writers like Deputy Nazir Ahmad, Ratan Nath Sarshar, and Premchand laid the foundation for socially conscious literature. Later, authors such as Ismat Chughtai, Saadat Hasan Manto, and Krishan Chander boldly addressed taboo subjects, psychological dilemmas, and social injustices. The Progressive Writers’ Movement played a pivotal role in intensifying this tradition. In the post-independence era, writers like Ahmed Nadeem Qasmi, Ashfaq Ahmad, Intizar Hussain, and Abdullah Hussain continued exploring the human condition amidst changing political realities. Female writers such as Hajra Masroor and Wajida Tabassum gave voice to women’s issues and challenged patriarchal norms. Urdu literature remains a vital space for critiquing societal structures and advocating reform, making it a reflective and transformative force in documenting and addressing the crises of its times. This abstract encapsulates the legacy of Urdu fiction in foregrounding contemporary issues through literary expression.